Draft Annual Plan Tamil Nadu 2012-2013 - Planning Commission (Planning Commission, 2012)
Tamil Nadu is one of the leading progressive states of the country with better socio-economic indicators. The State is committed to achieve higher sustainable economic and inclusive growth. As envisioned by the Hon’ble Chief Minister, the Government has come out with a vision document viz., Vision Tamil Nadu 2023 which aims to propel the State into the league of developed regions of the world and to the top of the league tables of Indian States. Tamil Nadu, given its factor endowments and the combination of strengths and opportunities, will aim to grow its GSDP at 11% or more per annum which is about 20% more than expected growth rate of India’s GDP (Vision 2023).
Government of Tamil Nadu, State Planning Commission
Government of Tamil Nadu